EFEKTIFITAS KOMBINASI TERAPI SLOW STROKE BACK MASSAGE DAN AKUPRESUR TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Nopri ' Afrila; Ari Pristiana Dewi; Erwin ' ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Hypertension is considered as a cardiovascular disease predicator and management of hypertension is required. Management of hypertension non pharmacological, one of which is slow stroke back massage and acupressure. The research aimed to determine the effectiveness of combination slow stroke massage and acupressure therapy for reducing blood pressure of hypertension patients. This research used quasy experiment design with non-equivalent control group. This research was conducted in Puskesmas Harapan Raya with 46 hypertension samples, which divided into 23 as experimental group and 23 as control group and chosen by cluster sampling technique. Experimental group was given combination slow stroke back massage and acupressure therapy for 15 minutes every session for three days, meanwhile control group were not. The blood pressure was measured with digital sphygmomanometer and observation sheet. The analysis used univariate by using frequencies and bivariate by using dependent t test and independent t test. The result of this research showed that reducing mean of mean artery pressure (MAP) in experiment group with 6,48 mmHg and reducing MAP in control group with 0,95 mmHg. Statistic analyze showed that was significant reducing blood pressure after giving intervention of experiment group with p value 0,000 (p<0,05). The conclusion is combination therapy effective for reducing blood pressure of hypertension and recommended to be applied for nursing intervention to reducing blood pressure of hypertension patients. Keywords: Acupressure, blood pressure, hypertension, slow stroke back massage